A Study on the Recognition of Students in Radiology on the Reorganization of Safety Management System by Nuclear Safety Act - Lee, Bo-Woo; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: The study developed a radiation dose measurement program in the radiology laboratory to measure how much exposure the students are exposed to during the radiology class, to request for the improvement and the revision of the current Nuclear Safety Act.Methods/Statistical analysis: The experimental program is shown in the following figure, and experiments were conducted to determine the degree of radiation exposure in the control room with a lead gown at a distance of 1m, 2m, and 1m, and in a control room with a radiographic lead glass wall. The duration of the experiment was 3 months from April to June, when radiation imaging practice classes were conducted, and 128 hours of imaging practice per month were conducted.Findings: In order to find out the dose of radiation dose during radiology imaging practice class, the experiment was carried out from April to June for 3 months, and according to the program, the results of exposure dose were 0.34mSv at 1m distance, 0.01mSv at shielding of lead gown at 1m distance, 0.16mSv at 2m distance, and 0.01mSv at control room with radiation lead glass wall. The exposure dose from the test results was much below the annual general public limit dose of 1mSv.Improvements/Applications: The restriction on the operation of the radiation equipment in the practice of the students is a regulation that infringes the right of students to learn, and amendments or exemptions of Nuclear Safety Act should be enacted to ensure that it does not violate the fundamental right to learn for students in radiology.Â Â